2021
DOI: 10.3390/ijerph18094663
|View full text |Cite
|
Sign up to set email alerts
|

Trends, Characteristics and Treatment Outcomes of Patients with Drug-Resistant Tuberculosis in Uzbekistan: 2013–2018

Abstract: Uzbekistan has a high burden of drug-resistant tuberculosis (TB). Although conventional treatment for multidrug-resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB) has been available since 2013, there has been no systematic documentation about its use and effectiveness. We therefore documented at national level the trends, characteristics, and outcomes of patients with drug-resistant TB enrolled for treatment from 2013–2018 and assessed risk factors for unfavorable treatment outcomes (death, failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
9
0
3
Order By: Relevance
“…TB regimens and dosing of required TB drugs were extracted from TB program guidelines for Karakalpakstan [54] and Uzbekistan [55], WHO guidelines [5], TB trial registrations on Clini-calTrials.gov [11][12][13][17][18][19], and MSF Access Campaign reporting. All-oral TB regimens were extracted from the MSF Access Campaign report 2020, TB regimens including an injectable antibiotic were extracted from MSF Access Campaign reports 2018-20 [42][43][44].…”
Section: Data Sourcesmentioning
confidence: 99%
“…TB regimens and dosing of required TB drugs were extracted from TB program guidelines for Karakalpakstan [54] and Uzbekistan [55], WHO guidelines [5], TB trial registrations on Clini-calTrials.gov [11][12][13][17][18][19], and MSF Access Campaign reporting. All-oral TB regimens were extracted from the MSF Access Campaign report 2020, TB regimens including an injectable antibiotic were extracted from MSF Access Campaign reports 2018-20 [42][43][44].…”
Section: Data Sourcesmentioning
confidence: 99%
“…MDR-TB patients which undergo Linezolid treatment was dominated by male (52.6%). A study by Safaev et al and Jaspard et al supported this result (7,12). This phenomenon could be explained by the increase susceptibility to infection that is caused by men related factors such as smoking that could cause toxic lung injury and reduced immune cell function and alcohol consumption that have immunosuppressive effects.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 86%
“…For instance, Atadjan et al stated that TB incidence showed a stable decline in the Russian Federation over the past 20 years, while Kozhoyarova et al revealed that there was a slow decline in TB mortality in Kyrgyzstan from 2007 to 2017 26 27. Safaev and coworkers informed that reported TB cases dropped significantly in Uzbekistan over the last 20 years 28…”
Section: Discussionmentioning
confidence: 99%